Vibration self-suppression of spinning fluid-conveying pipes composed of periodic composites. (15th April 2022) - Liang, Feng; Chen, Yao; Gong, Jun-Jie; Qian, Yu
Highlights: A novel phononic crystal model of fluid-conveying pipes with axially spinning motion is developed. Flexural wave motions in the orthogonally transverse directions trigger a 2D phononic crystal structure. A planar spectral element model of such spinning periodic pipes conveying fluid is established. Pseudo Bragg band gaps in different directions are found and effective band gaps are identified in their coupled regions. Complicated stability evolution and vibration mode of such spinning periodic structure are probed . Abstract: In this paper, a novel fluid-conveying phononic crystal (PC) pipe model is proposed. The pipe is composed of different materials arranged alternately, and an axially spinning motion is considered. The flexural wave motions along the orthogonally transverse directions trigger a two-dimensional (2D) PC structure. A planar spectral element (SE) model of the system is established, and the transverse free vibration and wave attenuation performance of such spinning periodic structure are explored thereby. The transfer matrix method is also utilized for validation. It is found that different pseudo Bragg band gaps (BGs) exist in the two transverse directions, while the effective BGs are actually located in their coupled regions, in which the vibration is truly self-suppressed. Such peculiar BG characteristic has not been theoretically revealed previously. Additionally, the spinning motion will reduce the effective BG regions of the periodic pipe. The impacts of the number of cells, flow velocity and component geometry on the natural frequencies and coupled BGs are also studied. The results obtained will provide theoretical basis and design reference for the potential applications of PC-type fluid-conveying devices. Graphical abstract: Image, graphical abstract